IFPRI 2020 Conference on "Leveraging agriculture for improving nutrition and health" - Paarlberg, Robert L. (International Food Policy Research Institute, 2013)
Since 1995, the 2020 Vision Initiative within IFPRI has organized periodic international multistakeholder Conferences for dialogue, debate, information sharing, and consensus building. The IFPRI 2020 Conference on “Leveraging Agriculture for Improving Nutrition and Health” was held in New Delhi, India, from February 10–12, 2011, and attracted more than 900 attendees. The Conference objective was to examine linkages among three intimately connected policy sectors: agriculture, nutrition, and health. IFPRI is a member of the CGIAR Consortium, a research network that has historically focused on agriculture rather than nutrition or health.